Homuncular mirrors: misunderstanding causality in embodied cognition - Mikulan, Ezequiel Pablo (2014)
Emerging theories on embodied cognition have caused high expectations, ambitious promises, and strong controversies. Several criticisms have been explained elsewhere (Mahon and Caramazza, 2008; Cardona et al., 2014) and will not be discussed further here. In this paper, we will focus on a specific explanatory strategy frequently assessed by the radical embodied cognition approaches: the use of homuncular explanations for the explicit (or implicit) attribution of causal roles in the comprehension of language understanding. We first present this criticism regarding a prototypical example: the mirror neuron system (MNS) (Rizzolatti and Craighero, 2004; Iacoboni and Dapretto, 2006) in the field of language understanding and then extend our conclusions to other programs of embodied cognition. Here we discuss the radical claims that propose the MNS as the putative mechanism for multiple cognitive and social psychology constructs (e.g., Gallese, 2008; Cattaneo and Rizzolatti, 2009; Iacoboni, 2009) and the critical role of the MNS in language understanding (Heyes, 2010a; Hickok, 2013).